2018
DOI: 10.1002/app.46924
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of poly(3‐hydroxybutyrate) with different thiol compounds inhibits MDM2–p53 interactions in MCF7 cells

Abstract: High-molecular-weight poly(3-hydroxybutyrate) (PHB) has a low reactivity toward its terminal functional groups. Thus, the chemical reactivity of PHB was enhanced by the chemical degradation that occurred via β-elimination through the functionalization of PHB with ethylene glycol to give a low-molecular-weight PHB-diol. The reaction of PHB-diol with acryloyl chloride gave PHB-diacrylate, which was grafted by thiol compounds, such as ethane dithiol, 2-mercaptoethanol, ethane thiol, dithiothreitol, butane thiol, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…Flow cytometry was applied to detect the influence of various treatments on cell number of each phase of the cell cycle as performed previously with some modifications. 34 Briefly, freshly dissected liver tissues were lysed by collagenase enzyme (0.1%, Invitrogen), then mesh filtered (0.7 mm nylon) and centrifuged (4000 rpm/5 min). After fixation, the cells were stained using propidium iodide and analyzed by Attune flow cytometer (Applied Bio-system).…”
Section: Cell Cycle Analysis By Flow Cytometrymentioning
confidence: 99%
“…Flow cytometry was applied to detect the influence of various treatments on cell number of each phase of the cell cycle as performed previously with some modifications. 34 Briefly, freshly dissected liver tissues were lysed by collagenase enzyme (0.1%, Invitrogen), then mesh filtered (0.7 mm nylon) and centrifuged (4000 rpm/5 min). After fixation, the cells were stained using propidium iodide and analyzed by Attune flow cytometer (Applied Bio-system).…”
Section: Cell Cycle Analysis By Flow Cytometrymentioning
confidence: 99%
“…Poly(3-hydroxybutyrate) (PHB) are the most thoroughly studied forms of biopolymer polyesters family for biomedical applications due to their biocompatibility, biodegradability, nontoxic, and adjustable mechanical properties. 18,19 These properties make PHB as an ideal candidate in medicine, surgery, pharmacology and in tissue engineering scaffolds. It was reported that PHB nanoparticles acted as an efficient carrier vehicle for doxorubicin drug and delayed the release for 5-7 days.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, PHAs are being used either as a blend or in its pure form in a variety of applications; scl-PHAs (short chain length) are predominantly used to produce food packaging and disposable items, and mcl-PHAs (medium chain length-characterized as elastomers) are appropriate for high value-added applications, such as surgical stitching, implants, and drug delivery systems [5,7,8]. There is also the opportunity to functionalize PHB chemically and/or enzymatically (as discussed later), which is among one of the most impervious polymers to be processed in certain plastic items [9]. Global use and industrialization of PHAs is limited due to high production costs, which results in higher prices than petrol-based polymers, such as polypropylene (PP) or polyethylene (PE), that have a price of approximately US $0.60–0.87/lb [10,11].…”
Section: Introductionmentioning
confidence: 99%